Wages, Profitability, and Growth in a Small Open Economy - Chadha, Bankim (IMF Working Papers; Working Paper ;, 1990)
This paper examines issues raised by the evolution of a rapidly growing small open economy-Singapore-from a labor-intensive, low-technology production base to a capital-intensive, high-technology, knowledge-and-skill-intensive emphasis as it approached the limits of its resource constraints in the labor market. In order to analyze the process of restructuring a model of endogenous growth for a small open economy that is driven by increases in labor productivity from learning and that allows for the dynamic acquisition of comparative advantage is developed. In this framework the effects of various policies and exogenous shocks on the direction and pace of restructuring are investigated.